Transformation Pattern Of Community Organization (Ormas) Into Group Violence in Jakarta - Pramono, Gatot Eddy (Technium Social Sciences Journal, 2020)
Community organizations (Organisasi Kemasyarakatan (Ormas)) in Jakarta are often involved in violence, such as conflict among them. The current study is a qualitative approach study with literature review and in-depth interviews as it is data collecting. Interviews were conducted at four organizations as a representative of the community organizations in Jakarta. They are Forum Betawi Rempug (FBR), Pemuda Pancasila, FORKABI, and Kembang Latar. Within the context of analysis, concepts such as sub-culture and conflict theory will be put to use. The result shows that community organizations transform into groups violence caused by three factors, which are group interests, disruption of group identity, and disruption of social organization